Revision of the South African genus Porophorus Schoenherr (Coleoptera: Curculionidae: Entiminae) - Borovec, Roman; Wanat, Marek (Zootaxa, 2026)
The genus Porophorus Schoenherr, 1845, with only one previously known species, P. odiosus Boheman, 1845, is redefined and compared with related genera. An additional thirty new species are described herein: P. abnormis Borovec and Wanat sp. nov. (South Africa: Western Cape); P. anysbergensis Borovec and Wanat sp. nov. (South Africa: Western Cape); P. appendiculatus Borovec and Wanat sp. nov. (South Africa: Western Cape); P. bituberculatus Borovec and Wanat sp. nov. (South Africa: Western Cape); P. brachysetosus Borovec and Wanat sp. nov. (South Africa: Western Cape); P. brunneofasciatus Borovec and Wanat sp. nov. (South Africa: Western Cape); P. brunneus Borovec and Wanat sp. nov. (South Africa: Northern Cape); P. calviniae Borovec and Wanat sp. nov. (South Africa: Northern Cape); P. canceris Borovec and Wanat sp. nov. (South Africa: Western Cape); P. elegans Borovec and Wanat sp. nov. (South Africa: Western Cape); P. elongatus Borovec and Wanat sp. nov. (South Africa: Western Cape); P. harani Borovec and Wanat sp. nov. (South Africa: Western Cape); P. hispidus Borovec and Wanat sp. nov. (South Africa: Western Cape); P. inflaticeps Borovec and Wanat sp. nov. (South Africa: Western Cape); P. maximus Borovec and Wanat sp. nov. (South Africa: Northern and Western Cape); P. montaguensis Borovec and Wanat sp. nov. (South Africa: Western Cape); P. muellerae Borovec and Wanat sp. nov. (South Africa: Western Cape); P. normalis Borovec and Wanat sp. nov. (South Africa: Western Cape); P. picturatus Borovec and Wanat sp. nov. (South Africa: Western Cape); P. probus Borovec and Wanat sp. nov. (South Africa: Western Cape); P. prochesi Borovec and Wanat sp. nov. (South Africa: Western Cape); P. salsolae Borovec and Wanat sp. nov. (South Africa: Western and Eastern Cape); P. spinulosus Borovec and Wanat sp. nov. (South Africa: Western and Eastern Cape); P. squamipennis Borovec and Wanat sp. nov. (South Africa: Western Cape); P. stalsi Borovec and Wanat sp. nov. (South Africa: Northern Cape, Namibia: Karas); P. subodiosus Borovec and Wanat sp. nov. (South Africa: Western Cape); P. tapetulus Borovec and Wanat sp. nov. (South Africa: Western Cape); P. variegatus Borovec and Wanat sp. nov. (South Africa: Western Cape); P. variicolor Borovec and Wanat sp. nov. (South Africa: Western Cape) and P. waboombergensis Borovec and Wanat sp. nov. (South Africa: Western Cape). All of the species are keyed and illustrated; male and female terminalia are described in detail, female genitalia for the first time; ecological information is presented where available. A lectotype is designated for Porophorus odiosus Boheman, 1845.